Yielding components in bean accessions - Barili, Leiri Daiane (2010)
The importance of genetic resources is widely recognized. The aim of this study was to evaluate the interrelation between grain yield and its components in accessions of common bean, as well as to determine which yelding component has the highest contribution in the grain yield among the different acessions evaluated. The experiment was carried out in Lages, Southern of Brazil, in the growing season of 2005/06, being constituted by 20 accessions of common bean. The path analysis was performed, including grain yield (basic variable) versus their primary components (secondary variables). Of the ten explanatory variables involved in the study, the number of racemes with legume per plant (NRL) was the only one presenting good combination between the direct effect and the correlation coefficient, both of significant values. Thus, the NRL is the most important component to predict grain yield in accessions of common bean, mainly for being of great value in the genetic progress of this character, through indirect selection.